Narrative Transformation Model of Kejhung and Macapat Oral Literature in The Digital Content Age - Badrih, Moh.; Siswiyanti, Frida; Murniatie, Itsnaniyah Umie (Universitas Muhammadiyah Malang, 2025)
Transforming Kejhung and Macapat into a digital format is a strategic step to expand the reach and preserve two traditional art forms rich in cultural values, especially among the younger generation. The main objective of this study is to analyze the digitalization process, level of acceptance, and understanding of the younger generation towards Kejhung and Macapat, which are packaged into 11 different digital platforms. The research method used is qualitative descriptive, with the support of quantitative data analysis, to obtain a comprehensive picture of the dynamics of this digitalization. The results of the study show that skills in using digital technology significantly influence cultural appreciation; it was recorded that 48.3% of respondents who were considered proficient in technology were able to create interactive content that aroused interest and understanding of traditional material. Although digital transformation opens up significant opportunities to revive traditional arts, serious challenges are related to the authenticity of the cultural values contained in Kejhung and Macapat. Therefore, this study concludes that technology-based innovation is needed that is not only oriented towards visual appeal, but can also maintain the essence and substance of cultural heritage to remain authentic and relevant for today's generation.